Influence of Temperature on the Fatigue Behaviour of a Toughened Epoxy Adhesive. Issue 7 (1st September 2016) - Beber, V.C.; Schneider, B.; Brede, M.
Abstract : Toughened epoxy adhesives are widely used for structural applications, especially in the design of lightweight products. During their service life, bonded joints are exposed to cyclic loading under a broad range of temperatures. In this study the influence of temperature on the fatigue behaviour of a toughened epoxy adhesive was investigated by experimental determination of SN curves under tension–tension cyclic loading. Bulk adhesive specimens and single lap, thick adherend and scarf joints were tested at a stress ratio of R = 0.1 and a frequency of f = 7 Hz at five different temperatures (−35°C, −10°C, RT, +50°C, +80°C). Dynamic mechanical analysis (DMA) was conducted to evaluate the temperatures of the phase transitions in the adhesive. Based on the experimental findings an interpolation method was proposed for estimating SN parameters at temperatures unaffected by phase transitions. The fatigue tests showed there was a reduction in fatigue lifetime with increasing temperature. DMA results indicated the adhesive underwent two phase transitions. The results from interpolations for different types of samples showed excellent agreement with the experimental findings, confirming the validity of the method, providing no phase transitions are within or close to the interpolation range.